2012
DOI: 10.1007/s11011-012-9296-8
|View full text |Cite
|
Sign up to set email alerts
|

Pathology supported genetic testing and treatment of cardiovascular disease in middle age for prevention of Alzheimer’s disease

Abstract: Chronic, multi-factorial conditions caused by a complex interaction between genetic and environmental risk factors frequently share common disease mechanisms, as evidenced by an overlap between genetic risk factors for cardiovascular disease (CVD) and Alzheimer’s disease (AD). Single nucleotide polymorphisms (SNPs) in several genes including ApoE, MTHFR, HFE and FTO are known to increase the risk of both conditions. The E4 allele of the ApoE polymorphism is the most extensively studied risk factor for AD and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 84 publications
(105 reference statements)
0
20
0
Order By: Relevance
“…For example, the ApoE 4 allele, a well-studied risk factor for AD, can increase the risk of coronary heart disease by approximately 40% [114]. …”
Section: Apoe4 Allelementioning
confidence: 99%
“…For example, the ApoE 4 allele, a well-studied risk factor for AD, can increase the risk of coronary heart disease by approximately 40% [114]. …”
Section: Apoe4 Allelementioning
confidence: 99%
“…120 In a study of middle-aged women, e4 carriers with higher cardiovascular fitness exhibited increased metabolism in the inferior temporal cortex and decreased metabolism in the middle and superior frontal gyri and right inferior parietal lobule when compared with lowfitness participants. 121 Interestingly, such differences were not found among non-carriers of the e4 allele, suggesting that physical activity may have a greater impact on the population at risk for AD/vascular disease.…”
Section: Cardiovascular Risk Factors and Cognitive Declinementioning
confidence: 99%
“…[6] Testing of the mutation panel underlying the high prevalence of FH in SA caused by a founder effect, [7] recurrent mutational events, [8] and population admixture, [9] may also be combined with apolipoprotein E (APOE) genotyping, to help distinguish between polygenic and monogenic FH. [10] PSGT provides an ideal framework for APOE genotyping in dyslipidaemics with a positive family history of late-onset Alzheimer's disease, incorporated as a novel component of the pre-screen algorithm developed by Lückhoff et al [11] Physical activity was shown to attenuate the cholesterol-raising effect of the APOE e-4 allele, recognised as a poor target for lipid-lowering pharmacotherapy in international studies. This SNP occurs in 30 -40% of the general population and affects lipid levels in a similar manner across ethnic groups.…”
Section: Single-gene Testing Of Founder Mutations and Snpsmentioning
confidence: 99%
“…At this important time in the history of human genetics, ethical concerns about genetic testing in SA were addressed in relation to a code of conduct compiled for the life insurance industry. [14] Analysis of thrombotic risk factors, individually or as part of a CVD multi-gene assay, [10] were evaluated in relation to: (i) the prevalence and penetrance of gene variants included in the test panel; and (ii) the potential benefits of preventative steps based on the findings. As a general rule, genetic testing will not have a negative effect when performed on the basis of well-defined selection criteria.…”
Section: Single-gene Testing Of Founder Mutations and Snpsmentioning
confidence: 99%